Human Capital and FDI Inflow: An Assessment of the African Case. (October 2015) - Cleeve, Emmanuel A.; Debrah, Yaw; Yiheyis, Zelealem
Highlights: This study drew on early works to provide a theoretical foundation. Investigates the factors that explain the inflow of FDI to Africa. The target variable is human capital, proxied by educational attainments. Uses a panel econometric analysis of 35 African countries over 1980–2012. Most proxies and control factors, e.g., natural resources, openness, determine FDI. Summary: This study assesses the role of human capital (HK) on FDI inflows to sub-Saharan Africa. It uses panel data for the period 1980–2012 to asses if changing skill needs influence FDI inflows. Several measures of HK are used to assess whether the quality of labor explains FDI flows over the study period. Various versions of an FDI model were estimated and the results show that all measures of HK have a significant influence on FDI, as are the traditional variables. There is no evidence of the increasing importance of HK on FDI over time, probably reflecting the type of FDI flowing into SSA.